Formulation elt~ments finis des ordonnees discretes pour Ia modelisation des transferts couples conduction-rayonnement en geometrie bidimensionnelle - Lope, Christine; Daurel, Jean-Vincent; Occelli, Rene (European Journal of Computational Mechanics, 1999)
Unlike the fin itt volumes formulation, widely associated with the discrete ordinates method, finite elements lwve been used by few authors in radiative heat transfer and semitransparent medium, even less in coupled transfers. We use the Ga/erkin finite elements formulation for the discre1e-ordinates to analyze the combined radiative and conductive heat transfer. The even paritv form is used, as it overcomes many problems associated with the classical primitive variables, as unrealistic negative intensities. The geometries sllldied are bidimensional and the medium is absorbing. emilling and/or scattering, enclosed bv gray or black walls. Our results are compared with those of litera/lire and of a finite volume code. Globally, the method shows peiformances similar to those of other approaches. Nevertheless, the finite elements have the advantage of filling naturally complex geometries.